THE APPLICATION OF INTERPRETIVE STRUCTURAL MODELING FOR CASH WAQF DEVELOPMENT STRATEGIES IN INDONESIA - Rusydiana, Aam (Universitas Airlangga, 2018)
This research is aim to identify the priority factors that being barrier to develop the practice of cash waqf in Indonesia using Interpretive Structural Modeling (ISM) method. The development of cash waqf in Indonesia with ISM framework is divided into three criteria: (1) Challenges (aspects) faced in developing cash waqf, (2) Strategy or foundation required within the framework of developing cash waqf, and (3) Stakeholders or actors involved in the development of cash waqf in Indonesia. Result show that the core problems and challenges faced in the development of cash waqf institution are: System aspect, product, regulation and information technology. The core strategies or foundations that's needed in framework of cash waqf development are: Transparency and accountability of waqf institutions, Quality development of nadzir, and Innovative marketing strategy from waqf institution. Government and Badan Wakaf Indonesia are stakeholders or actors involved and related to the development of cash waqf in IndonesiaKeywords: Cash Waqf, Management, Interpretive Structural Modeling, Indonesia Waqf